Ernesto Balducci, l’alterità e l’uomo planetario. Riflessioni pedagogiche tra comunicazione e formazione - Cosimo Di Bari (Studi sulla Formazione)
The article reflects on the thought of Ernesto Balducci starting from his ability to reflect between local and global dimensions and his “inhabiting” communication in an active and generative way. His thought is the bearer of various current insights for contemporary pedagogy, which can be related to authors who, before and after Balducci, have reflected on the need to educate, instruct and train the subject in order to make him or her a “citizen of the world”.